2008
DOI: 10.1029/2007jg000457
|View full text |Cite
|
Sign up to set email alerts
|

Sources of stream water sulfate during the spring snowmelt in boreal streams: Evidence from δ34S isotope measurements

Abstract: 2À during base flow conditions. Our results suggest that during the spring snowmelt, snow S and desorbing SO 4 of mainly anthropogenic origin are the two major S sources in four of the investigated streams. Two streams in forested areas also indicate that reoxidation of reduced S may be released during the spring flood. The stream in the cultivated area was found to be strongly influenced by the acid sulfuric soils independent of stream flow conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Their interpretation of these findings was that the drier conditions in the soils enhanced aeration of the soils and favored the oxidation of reduced sulfur species to the more mobile sulfate. Consequently, an increase in groundwater level releases more mobile sulfate, but the process appears to be slower because no rapid change in sulfate concentration was observed during the spring flood episodes. , A significant difference between sulfur and selenium is, however, that selenium is immobilized under less reducing conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their interpretation of these findings was that the drier conditions in the soils enhanced aeration of the soils and favored the oxidation of reduced sulfur species to the more mobile sulfate. Consequently, an increase in groundwater level releases more mobile sulfate, but the process appears to be slower because no rapid change in sulfate concentration was observed during the spring flood episodes. , A significant difference between sulfur and selenium is, however, that selenium is immobilized under less reducing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, an increase in groundwater level releases more mobile sulfate, but the process appears to be slower because no rapid change in sulfate concentration was observed during the spring flood episodes. 36,37 A significant difference between sulfur and selenium is, however, that selenium is immobilized under less reducing conditions. The proposed explanation suggests that the selenium concentrations in the stream are controlled by a narrow soil layer (as thin as a few centimeters) at the top of the saturated zone.…”
Section: ' Experimental Sectionmentioning
confidence: 99%
“…10). Using sulfur isotopes and sulfate concentrations in streams in northern Sweden, Mörth et al (2008) found that the main stream water sulfate sources were sedimentary sulfides and anthropogenic sulfur. During snowmelt, anthropogenic sulfur from the snow and desorbing sulfate were the main sources of sulfur.…”
Section: Water Chemistry: Long-term Trendsmentioning
confidence: 99%
“…One exemption to the general acidification recovery can be found in coastal areas of both Sweden and Finland that have undergone isostatic uplift. Ditching and other human activity in these post-glacial sediments has resulted in the oxidation of marine sulphur (Mörth et al, 2008;Åström, 2005) and the consequent acidification of many coastal streams (Österholm and Åström, 2002).…”
Section: Observations and Variabilitymentioning
confidence: 99%